An enhanced minimum variance distortionless response beamformer techniques to reduce interference in array antenna system - Shahab, Suhail Najm (2017)
Beamforming (BF) algorithm is one of the major smart antenna function that forming beams towards the direction of the desired user while simultaneously suppressing signals origination from other directions. Minimum Variance Distortionless Response (MVDR) is basically a unity gain adaptive beamformer which is suffering from performance degradation due to the presence of interference and noise. Also, MVDR is sensitive to the direction of arrival mismatch, and unsatisfactory null-forming level. This thesis presents two BF techniques to enhancing the MVDR null-forming level. First, the zero-null constraint adds to the MVDR beamformer based on uniform linear antenna arrays. The proposed MVDRZN is based on reconstructing the excitation weight vector coefficients to enforcing the undesired signal energy equal to zero (or near zero) and the desired signal energy equal to one (unity gain). Metaheuristic optimization algorithms are used widely to solve many engineering problems. Second, hybrid Particle Swarm Optimization/Gravitational Search Algorithm (PSOGSA) is used to obtain a desired radiation pattern by enhancing the MVDR nulling level. The proposed MVDRPSOGSA method combines the search methods of PSO and GSA, thus achieving the improved exploration ability needed to obtain high accuracy with deep null-forming in the directions of the interference sources. Whereas in the BF applications, Signal-to-Interference plus Noise Ratio (SINR) is a valid fitness function because it measures how well the array’s radiation pattern focuses energy on a Signal Of Interest (SOI) and steers nulls towards interference. In addition, to provide high accuracy beampattern and to enhance the null-forming level to suppress the interference and noise deeply. The performance of the proposed approaches is judged by the beampattern accuracy for azimuth and elevation scanning angles, SINR improvement through a deep null-forming level. The null width in the azimuth and elevation scanning angle also have been assessed. The result shows that the proposed MVDRZN method clearly introduce more than 300 dB negative power to serve the interference source with average SINR improvements approximately 250 dB and accurate azimuth and elevation angles. It is observed that the MVDRZN can provide a perfect radiation pattern with relatively few snapshots records. The obtained results confirm the complete agreement between MVDR technique and hybrid intelligent swarm PSOGSA algorithm. The proposed MVDRPSOGSA approach can successfully place very sharp nulls (-200 dB deep, on average) at the undesired angles. It is providing additional support to the smart antenna array system to combat the co-channel interference and array noise reduction. These approaches achieve significant SINR improvement by reducing the effects of multiple access interference in the wireless communication systems.